2021
DOI: 10.1152/japplphysiol.00144.2020
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variability in the upper tracheobronchial tree: sex-based differences and implications for personalized inhalation therapies

Abstract: The morphometry of the large conducting airways is presumed to have a strong effect on the regional deposition of inhaled aerosol particles. Nevertheless, sex-based differences have not been fully quantified and are still largely ignored in designing inhalation therapies. To this end, we retrospectively analyzed high-resolution computer-tomography scans for 185 individuals (90 women, 95 men) in the age range of 12−89 years to determine airway luminal areas, airway lengths and bifurcation angles. Only subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…Studies involving x-ray and acoustic reflectance measures noted that tracheal area was smaller in females than in males [43,44]. Recently, studies involving computed tomography imaging demonstrated that females have smaller central conducting airways (i.e., trachea to third generation bronchi) and the difference persists when subjects are matched for lung size [18,19] or height [17]. Upstream of the ∼third generation, the magnitude of sex differences in airway size decreases; however, this may be due to the size of these airways approaching the resolution limits of computed tomography.…”
Section: Central Conducting Airwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving x-ray and acoustic reflectance measures noted that tracheal area was smaller in females than in males [43,44]. Recently, studies involving computed tomography imaging demonstrated that females have smaller central conducting airways (i.e., trachea to third generation bronchi) and the difference persists when subjects are matched for lung size [18,19] or height [17]. Upstream of the ∼third generation, the magnitude of sex differences in airway size decreases; however, this may be due to the size of these airways approaching the resolution limits of computed tomography.…”
Section: Central Conducting Airwaysmentioning
confidence: 99%
“…• Males above the age of ∼14 years have proportionally greater airway luminal area of the large conducting airway (i.e., trachea to the third generation) than females [15,[17][18][19][20] • Males have larger absolute lung volumes and more alveoli than females [9, 21] • Females have "prismatic" geometry of the ribcage and lung while males have "pyramidal" ribcage and lung geometry [22][23][24] Functional differences • Higher W b and V ̇O2 RM for a given absolute V ̇E during exercise in females compared to males [10,13,53-27] Due to a higher resistive component of W b [25,[28][29][30] • Females have greater activation of "extra-diaphragmatic" inspiratory muscles for a relative or absolute V ̇E during exercise Noted in the scalene and sternocleidomastoid muscles [31,32] • Highly trained males are less likely to develop expiratory flow limitation during exercise than highly trained females [13,25] • Females have a blunted respiratory muscle metaboreflex [33][34][35][36][37] • EIAH can occur in untrained females but does not appear to occur in untrained males [38][39][40] • Older females have a higher perception of dyspnoea at absolute and relative exercise intensities than older males [10,11,41] EIAH: exercise-induced arterial hypoxaemia; V ̇E: minute ventilation; V ̇O2 RM : oxygen uptake of the respiratory muscles; W b : work of breathing.…”
Section: Morphological Differencesmentioning
confidence: 99%
“…In addition, emphysema might have also played a role, because emphysema is signi cantly associated with reduced BMI (24), and is also more common in male patients (25). Furthermore, sex-modi ed effects of BMI on FEV 1 decline may be related to anatomical differences in the large airways that have been observed between men and women, such as smaller central airways and lower thoracic volume in females (26,27). Due to concerns regarding reverse causality, we were unable to study the effects of dynamic changes in BMI (i.e., increased lung burden caused weight loss).…”
Section: Discussionmentioning
confidence: 99%
“…3DP plays a crucial role in the management of complex respiratory diseases. The high variability in the anatomy of the tracheobronchial tree [ 109 ] makes standardized interventional treatments very challenging especially for stent placement.…”
Section: Surgical Applicationsmentioning
confidence: 99%